Making machine learning matter to clinicians: model actionability in medical decision-making - Daniel E. Ehrmann; Shalmali Joshi; Sebastian D. Goodfellow; Mjaye L. Mazwi; Danny Eytan (npj Digital Medicine, 2023)
Abstract Machine learning (ML) has the potential to transform patient care and outcomes. However, there are important differences between measuring the performance of ML models in silico and usefulness at the point of care. One lens to use to evaluate models during early development is actionability, which is currently undervalued. We propose a metric for actionability intended to be used before the evaluation of calibration and ultimately decision curve analysis and calculation of net benefit. Our metric should be viewed as part of an overarching effort to increase the number of pragmatic tools that identify a model’s possible clinical impacts.